Purchase Intention: Apakah Brand Experience dan Brand Image mempengaruhi? (Studi Empirik pada Aplikasi Gopay) - Susanto, Tia Vincent; Siagian, Dergibson (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
The development of technology today has brought changes to people's daily lives. One of these changes is how people make cash transactions, where people are directed to make cashless transactions or without using physical cash. The object of this study is GoPay, a local e-wallet brand, with the research location in the city of Jakarta. The purpose of this study is to determine the effect of brand experience and brand image on purchase intention. The data collection technique uses communication techniques with the help of questionnaire instruments distributed electronically via Google Form to 108 respondents. The sampling technique used is judgment sampling. The results of this study are that brand experience and brand image have a positive and significant effect on purchase intention.